Inclusion of Identity’s Formation and Diverse Sexual Orientation in Socio-Emotional Learning Programs of Secondary Education - Ramos-Monsivais, Cynthia Lizeth (2023)
Introduction. Education is a process of comprehensive training of individuals. It requires permanent updating to meet the demands of today’s society. It is also a means to build inclusive societies, strengthen, and promote well-being and social development. Objective. This essay aims to reflect on diverse sexual orientation as a social and cultural difference that impacts people’s mental health and well-being due to the lack of personal acceptance and social rejection. Development. Education can contribute to create inclusive communities and promote mental health. From the formative process of secondary education, the development of socio-emotional skills and character strengths can promote the mental health of students. Conclusion. As a result of the review and theoretical discussion, this essay proposes the inclusion of self-acceptance as an emotional intelligence competence. In addition, socio-emotional learning during secondary education can help develop this competence via orientation, workshops, and social support groups for students and their families.